A common fixed point theorem of Meir and Keeler type - Y. J. Cho; P. P. Murthy; G. Jungck (International Journal of Mathematics and Mathematical Sciences)
In this paper, we introduce the concept of compatible mappings of type (A) on a metric space, which is equivalent to the concept of compatible mappings under some conditions, and give a common fixed point theorem of Meir and Keeler type. Our result extends, generalized and improves some results of Meir-Keeler, Park-Bae, Park-Rhoades, Pant and Rao-Rao, etc.